Meningkatkan Keterampilan Motorik Halus Melalui Kegiatan Menggunting pada Anak Tunagrahita Sedang - Rubayyi Nadila; Jon Efendi (Dinasti Research, 2020)
This research was conducted based on the findings of problems in mentally retarded students in class V SLBN 1 Padang. Children's fine motor skills are still low. So the purpose of this research is to improve the fine motor skills of mentally retarded students through scissors activities. This research uses Single Subject Research with an A-B-A reversal design. Observations and measurements at the baseline (A1) were carried out 4 times to obtain data on the child's initial ability before the intervention was carried out. Intervention (B) was carried out 7 times where children were given treatment through cutting activities. Then do the baseline (A2) 4 times to get data on the child's abilities after being given the intervention. Data were collected using action test instruments and data were analyzed visually and graphically. The results of the data analysis show a positive rate of change. This means that the child's fine motor skills are increasing.